2001
DOI: 10.1016/s0092-8674(01)00577-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated Glycosylation of the CD8αβ Coreceptor Stalk Modulates Ligand Binding

Abstract: The functional consequences of glycan structural changes associated with cellular differentiation are ill defined. Herein, we investigate the role of glycan adducts to the O-glycosylated polypeptide stalk tethering the CD8alphabeta coreceptor to the thymocyte surface. We show that immature CD4(+)CD8(+) double-positive thymocytes bind MHCI tetramers more avidly than mature CD8 single-positive thymocytes, and that this differential binding is governed by developmentally programmed O-glycan modification controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
202
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(217 citation statements)
references
References 54 publications
13
202
1
1
Order By: Relevance
“…Different patterns of sialylation were found in different thymocyte subsets as well as the expression of sialyl transferases (1,2,35). Peanut agglutinin-binding properties vary from cortical to medullary thymocytes in association with sialic acid acquisition on the cell surface (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different patterns of sialylation were found in different thymocyte subsets as well as the expression of sialyl transferases (1,2,35). Peanut agglutinin-binding properties vary from cortical to medullary thymocytes in association with sialic acid acquisition on the cell surface (1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an exogenous ␣2-3 sialyltransferase-like activity mediated by TS and working at the thymocyte vicinity may modify the cell surface, mimicking the endogenous expression of the equivalent enzyme, although in the wrong place and͞or at the wrong time. Exogenous modifications of the surface sialyl-residue pattern might be crucial to decide the final fate of the cells altered by positive͞negative selection interference or interaction with thymic lectins (3,35,36). The enzyme acts by mobilization of the sialyl residue, leading to either acquisition or loss of the residue by transferring it among glycoconjugates of the same cell, among different cells, or to the milieu.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the individual TCR⅐CD3 subunits could possess slightly distinct structures. These differences could be caused by developmentally acquired fundamental changes that distinguish the two cell types, including the glycosylation machinery (30,31) or chaperones. For instance, the inactivation of a sialyltransferase (ST3Gal-I) strongly reduced peripheral CD8 ϩ but not CD4 ϩ cell numbers (32).…”
Section: Fig 6 Characterization Of the Rw2-8c8 Antibody A Purifiedmentioning
confidence: 99%
“…It is also possible that one specific binding mode might be better accommodated because of the particular position at which a specific TCR docks with pMHCI (29 -31). Furthermore, the differentiation stage-related sialylation of the O-glycans associated with the stalk regions of CD8 proteins (18,19) may be compatible with one, but not another, binding orientation. Therefore, a given TCR⅐pMHCI complex may preferentially or exclusively interact with CD8␣␤ in one binding mode but not the other.…”
Section: Discussionmentioning
confidence: 97%
“…We reported previously that the extracellular domain of the CD8␤ subunit is critical for this enhanced efficiency (14) and that introduction of the CD8␤ stalk region is sufficient to confer a CD8␣␤-like co-receptor efficiency to the CD8␣␣ homodimer (17). In addition, the sialylation of the O-linked glycans in the CD8␤ stalk region is differentiation stage-dependent and may modulate the intrinsic activity of CD8␣␤ during the transition from double-positive (CD4 ϩ CD8 ϩ ) to single-positive (CD8 ϩ ) T cells (18,19). It was also reported that palmitoylation of a membrane-proximal cysteine residue in the cytoplasmic tail of CD8␤ during T-cell activation facilitates partition of CD8␣␤ heterodimers into lipid rafts, where it associates with the CD3 component of TCR complexes (20).…”
mentioning
confidence: 99%